Y2k... 2000 and dioxins. a part of our natural ecosystem - TYRPENOU, A. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
The new millennium, Y2k as it is internationally symbolized, has come closer, and as doomsayers use to say "Plan for the worst in order to hope for the best". Starting up from the scandal of the identification of high concentrations of dioxin residues in foods of animal origin, it is imperative to refer to this group of chemical pollutants which they have been, they are and they will be the focus of the interest for many years to come. Polychlorinated dibenzo-para-dioxins [PCDDs] and polychlorinated dibenzofuranes [PCDFs] are by-products of industrial processes for the production of organochlorine pesticides [OCPs], polychlorinated biphenyls [PCBs], wood conservation industries, chlorine bleaching of pulp and paper industries, but also the result of municipal solid waste management [MSW] with special attention to recycling processes whose environmental emission are extremely high. From the other hand, we should have to realize that dioxins have been a natural contaminant of our environment for more than 60 million years. Taking into consideration the Tolerable Daily Intake [TDI], which has been set to 1 pg-4pg I-TEQ/kg.b.w. [quantity which includes together dioxins, furans and polychlorinated biphenyls], based on their mode of action and toxicity, it is obvious that the measures which the competent authorities of every country have to put in place for the control of raw materials and food of animal origin, should have to be strict, systematic, permanent and reliable so that they safeguard consumer’s health as better as they can.